Processing of Plastics Waste into Fuel Oil by Communal Scale Pyrolysis Method in Kedungringin Village, Muncar, Banyuwangi - Prabuditya Bhisma Wisnu Wardhana; Agung Fauzi Hanafi; Asmar Finali; Mega Lazuardi Umar; Andrean Bagus Prasetyo (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
Plastic waste is a big problem in society because it can pollute the environment. The purpose of this assisted village grant program is to apply plastic waste processing technology into fuels that can be used for household and small-scale industrial purposes for the residents of Kedungringin village. The activities of the assisted village grant program are carried out by observing partners, then identifying equipment needs and designing and fabricating pyrolysis equipment. After the fabrication process is complete, then it is continued with socialization and training for Kedungringin villagers. Reactor performing tests using 1.5 kg of polyethylene plastic waste were able to produce about ± 1.2 liters of oil and ± 200 grams of charcoal from plastic waste. We hoped that with this plastic waste processing tool, the problem of environmental pollution due to the accumulation of plastic waste can be solved without causing new problems.